Estudo dos impactos do corte seletivo de árvores na diversidade genética e demografia de população de araucaria angustifolia, utilizando modelagem ecogene - Dal Bem, Edjair Augusto [UNESP] (2014)
Araucaria angustifolia is a conifer, dioecious and wind pollinated tree economically important in the southeastern and southern Brazil. In the past century, the species was heavily exploited by the regime of clear-cutting, and today there are less than 3% of its original forests. Furthermore, recently, rose the chance to re-explore the remaining forests of A. angustifolia, using reduced impact logging (RIL) procurements. The Eco-gene model was used to investigate the long-term impacts of logging on the demography and genetic diversity of A. angustifolia populations and to determine what are the scenarios of selective logging that ensure sustainable production of wood and not drastically affect the genetic diversity of exploited populations. The study was conducted with data from microsatellite loci, demographic, ecological and dendrometric of a small fragmented population of A. angustifolia. In this research, different scenarios of selective cutting, which represent combinations of different minimum cutting diameter (MCD), intensity of exploitation (IE) and cutting cycle (CC) were studied. Based on the results, selective logging showed two main effects on the populations: (a) reduction in the total number of reproductive individuals (N), b) increase in genetic distance between the original population and after cycles court and the number of unilocus genotypes. The average number of individuals (N) for scenario control after 122 years was 515. For DMC of 50 cm and IE 20, 40 and 90%, after four cycles of cutting and the year of the fifth cutting, the N was 476 (-7.7%), 441 (-14.4%) and 415 (-19.5% ), respectively. For the DMC 75 cm, N was reduced for the three IE from 9.0 to 10.4% and for DMC and 100 cm, from 4.8 to 5.8%. Therefore, smaller IE, result in fewer individuals being explored and less difference compared to a situation without selective logging (control). For DMC of 50 cm and IE 20, 40 and 90%, ...